(untitled) (Indonesian Journal of Agrarian Law, 2026)
River abrasion is one of the natural events that can cause changes in the physical condition of land, or even result in the complete disappearance of land. This situation raises legal issues, particularly for communities that hold Certificate of Ownership (Sertipikat Hak Milik) over land subsequently affected by abrasion. This problem occurs in Sriamur Village, North Tambun District, Bekasi Regency, where abrasion of the Bekasi River has caused a reduction in land area and even the loss of several land plots belonging to residents. This study aims to analyze the legal status of land affected by abrasion as well as the forms of legal protection for holders of the Certificate of Ownership over such land. The research employs a juridical-empirical approach by examining laws and regulations related to land rights, rivers, and the environment, supported by field data obtained through interviews with affected residents and relevant agencies. The results show that river abrasion may cause land to be classified as destroyed land (tanah musnah) if it can no longer be identified, thereby extinguishing the land rights and reverting them to state control. However, in practice, there remains legal uncertainty due to the absence of an official determination of destroyed land and the lack of a compensation mechanism for communities whose land has been reduced or has fallen into the river border area.